C-reactive protein concentrations are higher in dogs with stage IV chronic kidney disease treated with intermittent hemodialysis - Picelli de Azevedo, Maria Gabriela [UNESP]; Salgueiro Geraldes, Silvano [UNESP]; Bilbau Sant'Anna, Paula; Poloni Batista, Beatriz; Rodrigues Maia, Suellen [UNESP]; Silveira de Moraes, Reiner [UNESP]; Moreira Dos Santos Schmidt, Elizabeth [UNESP]; Ferreira de Souza, Fabiana [UNESP]; Melchert, Alessandra [UNESP]; Pinheiro Ferreira, João Carlos [UNESP]; Rezende Dadalto, Carmel [UNESP]; Mogollón García, Henry David [UNESP]; et al. (Public Library of Science (PLoS), 2022)
In chronic kidney disease dogs, the inflammatory process increases C-reactive protein concentrations. This study aimed to determine C-reactive protein serum concentrations in stage IV chronic kidney disease dogs treated with intermittent hemodialysis. A prospective cohort study was conducted with 23 dogs allocated into three groups: control group (CG, n = 7), intermittent hemodialysis group (IHG, n = 8) and clinical treatment group (CTG, n = 8), both comprised of stage IV chronic kidney disease dogs. One blood sample from CG (initial evaluation) and two samples from IHG and CTG (first- and last-moment) were obtained to determine C-reactive protein concentration, total leukocytes, platelets, erythrocytes, total plasma protein, serum albumin, urea, creatinine, and phosphorus. C-reactive protein was higher in IHG compared to CG in the first- and last-moments (p <0.001) and compared to CTG in the first-moment (p = 0.0406). C-reactive protein presented moderate positive correlation with leukocytes (r = 0.5479; p = 0.01), and moderate negative correlation with albumin (r = - 0.5974; p = 0.006) and red blood cells (r = - 0.5878, p = 0.01). A high correlation coefficient was observed in the tests' evaluation (CI = 0.59-0.78; r = 0.70; P<0.0001). In conclusion, both assays used in this study to measure C-reactive protein have provided safe and reliable quantification of the results. Additionally, despite IHG dogs presented an active inflammatory profile, intermittent hemodialysis has proven to be beneficial, leading to a clinical improvement in life quality of patients, and thus being recommended for stage IV CKD dogs when performed by trained professionals.